The impact of implementation approaches in activity-based workplace transitions: a mixed methods study in the Swedish public sector - Pär Löfstrand; Stig Vinberg (Cogent Psychology)
Activity-based workplaces, implemented in conjunction with working from home, are likely to become more prevalent in the future. Research on these environments remains limited within public sector workplaces. This study employs a mixed methods design to examine transition processes to these environments in Swedish public sector workplaces. Employees from the same organization were drawn from two offices at different locations, both of which had transitioned to activity-based workplaces One group using a broad strategy served as the intervention group (N = 282, 79% women), while the other using an expert driven strategy acted as the reference group (N = 157, 84% women). The employees represented various administrative operations. Findings reveal that, when comparing employees in the intervention group with the reference group undergoing this transition, the former group outperformed the latter group. Participants in the intervention group rated the transition processes, workplace communication and support from managers during the processes and various organizational, social, and individual factors significantly higher than those in the reference group. Qualitative findings highlight both positive and negative expectations, as well as the risks and opportunities associated with activity-based and working from home environments. Implications regarding these environments are that a well-executed implementation process during organizational change is essential for achieving favorable process outcomes. Of importance is to ensure sufficient time for the transition processes and actively engage managers and employees throughout the process to foster positive outcomes.